Examination of the relationship between health literacy, concern and anxiety in adults with diabetes mellitus or hypertension and comparison with individuals without chronic disease - Beyoğlu, Muhammed Mustafa; Avcı, Dilek (Journal of Surgery and Medicine, 2020)
Aim: The low level of health literacy in our country can cause worry and anxiety. The effect of this situation in individuals with chronic diseases was compared with healthy individuals. In our study, the level of health literacy (HL) of individuals with a chronic disease (Diabetes Mellitus (DM) or Hypertension (HT)) who applied to the Family Medicine outpatient clinic was determined. The effect of HL on anxiety levels in individuals with and without chronic diseases was investigated. Methods: This cross-sectional study included those with chronic diseases (DM or HT) and healthy individuals. The data were obtained with Adult Health Literacy Scale (AHLS), Anxiety, Anxiety Scale (WAS) and descriptive questionnaire. SPSS 22 statistics program was used for statistical analysis. Descriptive statistics, chi-square analysis, ANOVA and Pearson correlation analysis were used in statistical evaluation. Results: The mean scores of Adult Health Literacy Scale (AHLS) were 6.21 for individuals with HT, 6.58 for individuals with DM and 14.92 for healthy subjects. The mean scores of Worry and Anxiety Scale (WAS) were 46.42 in individuals with HT, 44.54 in individuals with DM and 34.19 in healthy individuals. The scores of scales were significantly different among individuals with and without chronic diseases (DM or HT) (P<0.01). A significant negative correlation was found between the scores of WAS and AHLS among individuals with DM and HT (P<0.01, P<0.01, r=-0.35, r=-0.45, respectively). Conclusion: This study showed that individuals with DM and HT had lower health literacy levels and higher worry and anxiety scores than healthy individuals. It was found that low health literacy level was associated with chronic diseases and inversely related to worry and anxiety.